MORFOLOGI DAN KLASIFIKASI TANAH DI LERENG UTARA GUNUNG SINABUNG KABUPATEN KARO SUMATERA UTARA - Ridwandi Ridwandi; Muklis Muklis; Mariani Sembiring (Universitas Sumatera Utara, 2013)
The survey research is aimed to know the morphology and classification of soils at north slope ofMt.Sinabung. This research was conducted in Subdistrict Naman Teran, District Karo, NorthSumatera Province. Three selected pedons were observed at top slope, middle slope, and bottomslope. Soil samples were taken from each horizon for analysis soil texture, bulkdensity, pH H2O,pH KCl, pH NaF, Aldd, Base Saturation, CEC, ZPC (Zero Point of Charge), Organiccontent, P-retention, P-total, Al-oxsalate extracted (Alo), Si-oxsalate extracted (Sio), and Feoxsalateextracted (Feo) in The Chemical Soil Fertility and Research and Technology Laboratory,Agricultural Faculty of North Sumatera University, Medan. The result of the observation and theanalysis showed that the top slope soil has a rock material of lava which has been solid through ashallow solum, the middle slope soil have a perent material of lahars through a thick solum, and thebottom slope soil have a parent material of volcanic ash through a thick solum. According to SoilTaxonomy, the top slope soil is classified into su group Andic Dystrudept, however both of themiddle slope soil and the bottom slope soil are classified into sub group Typic Hapludand.Key Word : Mt.sinabung, soil classification. Soil morphology